2004
DOI: 10.1095/biolreprod.103.026328
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Morphology of the Penis in Male Rats Exposed Neonatally to Diethylstilbestrol Is Associated with Altered Profile of Estrogen Receptor-α Protein, but Not of Androgen Receptor Protein: A Developmental and Immunocytochemical Study1

Abstract: Objectives of the study were to determine developmental changes in morphology and expression of androgen receptor (AR) and estrogen receptor (ER)alpha in the body of the rat penis exposed neonatally to diethylstilbestrol (DES). Male pups received DES at a dose of 10 microg per rat on alternate days from Postnatal Day 2 to Postnatal Day 12. Controls received olive oil vehicle only. Tissue samples were collected on Days 18 (prepuberty), 41 (puberty), and 120 (adult) of age. DES-induced abnormalities were evident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 51 publications
7
54
0
Order By: Relevance
“…One potential mechanism by which neonatal estrogen exposure induces developmental abnormalities may involve an activation of ERa-mediated signaling because we previously found an association between ERa upregulation and penile abnormalities in the developing rat penis treated neonatally with DES (Goyal et al 2004b(Goyal et al , 2005b. Similarly, ERa upregulation is associated with abnormal development of rodent female reproductive tract (Yamashita et al 1990, Markey et al 2005, mammary gland (Tekmal et al 2005), male reproductive tract (Sato et al 1994), prostate gland (Prins & Birch 1997, and seminal vesicles .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…One potential mechanism by which neonatal estrogen exposure induces developmental abnormalities may involve an activation of ERa-mediated signaling because we previously found an association between ERa upregulation and penile abnormalities in the developing rat penis treated neonatally with DES (Goyal et al 2004b(Goyal et al , 2005b. Similarly, ERa upregulation is associated with abnormal development of rodent female reproductive tract (Yamashita et al 1990, Markey et al 2005, mammary gland (Tekmal et al 2005), male reproductive tract (Sato et al 1994), prostate gland (Prins & Birch 1997, and seminal vesicles .…”
Section: Discussionmentioning
confidence: 83%
“…Another mechanism of estrogen-inducible, developmental penile abnormalities may involve alterations in androgen action because androgen receptors are ubiquitously present in the rat penis (Goyal et al 2004b), and their concentration is maximal prior to puberty (Rajfer et al 1980, Takane et al 1990). Additionally, neonatal estrogen exposure downregulates androgen receptor level in male reproductive organs (Prins & Birch 1995, Woodham et al 2003 and lowers plasma testosterone (Sharpe et al 1998, Atanassova et al 2000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, bisphenol A has been shown to accelerate terminal differentiation of 3T3L1 fibroblasts into adipocytes through the PI 3 kinse pathway [34]. Interestingly, in developmental studies, Goyal et al [35][36][37][38] have shown that administration of estradiol valerate or the estrogen receptor agonist diethylstilbestrol into 2-day-old rats resulted in infertile mature animals (120 d) and accumulation of fat-containing cells in the penile corpus cavernosum. In contrast, animals treated with vehicle exhibited no fat-containing cells and remained fertile.…”
Section: Testosterone Regulates Cellular Growth and Differentiationmentioning
confidence: 99%
“…Hypospadias is currently repaired by pediatric surgery (Baskin, 2001). As for estrogen-dependent processes of differentiation, its effect on male urogenital organ formation also still remains poorly described (Hess, 2003;Pu et al, 2004;Huang et al, 2005;Goyal et al, 2004).…”
Section: The Differentiation Of the Gt: Urethra Penis And Clitoris mentioning
confidence: 99%